Influence of Rootstock Genotype and Ploidy Level on Common Clementine (Citrus clementina Hort. ex Tan) Tolerance to Nutrient Deficiency - Oustric, Julie; Herbette, Stéphane; Morillon, Raphaël; Giannettini, Jean; Berti, Liliane; Santini, Jérémie (Frontiers in Plant Science, 2021)
Nutrient deficiency, in particular when this involves a major macronutrient (N, P and K), is a limiting factor on the performance of plants in their natural habitat and agricultural environment. In the citrus industry, one of the eco-friendliest techniques for improving tolerance to biotic and abiotic stress is based on the grafting of a rootstock and a scion of economic interest. Scion tolerance may be improved by a tetraploid rootstock. The purpose of this study was to highlight if tolerance of a common clementine scion (C) (Citrus clementina Hort. ex Tan) to nutrient deficiency could be improved by several diploid (2x) and their tetraploid (4x) counterparts citrus genotypes commonly used as rootstocks: Trifoliate orange x Cleopatra mandarin (C/PMC2x and C/PMC4x), Carrizo citrange (C/CC2x and C/CC4x), Citrumelo 4475 (C/CM2x and C/CM4x). The allotetraploid FlhorAG1 (C/FL4x) was also included in the experimental design. The impact of nutrient deficiency on these seven scion/rootstock combinations was evaluated at root and leaf levels by investigating anatomical parameters, photosynthetic properties and oxidative and antioxidant metabolism. Nutrient deficiency affects foliar tissues, physiological parameters and oxidative metabolism in leaves and roots in different ways depending on the rootstock genotype and ploidy level. The best known nutrient deficiency-tolerant common clementine scions were grafted with the doubled diploid Citrumelo 4475 (C/CM4x) and the allotetraploid FlhorAG1 (C/FL4x). These combinations were found to have less foliar damage, fewer changes of photosynthetic processes (leaf net photosynthetic rate (Pnet), stomatal conductance (gs), transpiration (E), maximum quantum efficiency of PSII (Fv/Fm), electron transport rate (ETR), ETR/Pnet), and effective quantum yield of PSII (Y(II))), less malondialdehyde accumulation in leaves and better functional enzymatic and non-enzymatic antioxidant systems. Common clementine scions grafted on other 4x rootstocks did not show better tolerance than those grafted on their 2x counterparts. Chromosome doubling of rootstocks did not systematically improve the tolerance of the common clementine scion to nutrient deficiency.